The States of Pluripotency: Pluripotent Lineage Development in the Embryo and in the Dish. (24th March 2014) - Rathjen, Joy
Abstract : The pluripotent cell lineage of the embryo comprises a series of temporally and functionally distinct intermediary cell states, the epiblast precursor cell of the newly formed blastocyst, the epiblast population of the inner cell mass, and the early and late epiblast of the postimplantation embryo, referred to here as early and late primitive ectoderm. Pluripotent cell populations representative of the embryonic populations can be formed in culture. Although multiple pluripotent cell states are now recognised, little is known about the signals and pathways that progress cells from the epiblast precursor cell to the late primitive ectoderm in the embryo or in culture. The characterisation of cell states is most advanced in mouse where conditions for culturing distinct pluripotent cell states are well established and embryonic material is accessible. This review will focus on the pluripotent cell states present during embryonic development in the mouse and what is known of the mechanisms that regulate the progression of the lineage from the epiblast precursor cell and the ground state of pluripotency to the late primitive ectoderm present immediately prior to cell differentiation.